PELATIHAN KOMUNIKASI KONSELING PADA ASISTEN KONSELOR DI BIRO LAYANAN BIMBINGAN DAN KONSELING (BLBK)FAKULTAS TARBIYAH DAN KEGURUAN IAIN ANTASARI BANJARMASIN - Masyitah, Masyitah (Tarbiyah, 2014)
In order to improve the service of the Bureau of Guidance and Conselling Services of Tarbiyah and Teachers Training Faculty of IAIN Antasari Banjarmasin, the bureau has recruited 15 counselors assistant since 2013. Counselling Communication training is conducted to equip those counselors assistant. This research is intended to describe the implementation of that counselling communication training ad the result of this training for the participants. This research used qualitative approach and used observation, test, interview, and documents to collect the data. Overall, the training run well, and the test result showed that the ability to hearof the majority subject (73% of the subject) is on the average level, while all of them (100%) are above standard level on the ability to communicate. Furthermore, based on the evaluation and reflection, the participants stated that: 1) they got new experience and deepening their understanding on the training material, 2) they did not get counseling practice experience while studying at the department, 3) they are interested in with the quiz for measuring communication competence, and 4) they got experience in self expression through counseling and reflection part at the end of training.Keyword: training, communication counseling, councelor assistant, counseling practice